(untitled) (Acta Academica: Critical views on society, culture and politics, 2012)
Education reform in many parts of the world is premised on the view that teachers show lack of professionalism. The solution to this problem lies in increasing teacher professionalism. Education reform, therefore, affects how teachers view themselves as professionals, their work and their effectiveness, and how they compose their identities in schools. The study aims to investigate the perceptions of teachers with regard to the extent to which they practise professionalism in their schools. The data collected tended to refute the view expressed in the literature that teachers lack professionalism